2009
DOI: 10.3390/s91108613
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of Bread Production with Postponed Staling Applying Instrumental Measurements of Bread Crumb Color

Abstract: Crumb color quality characteristics of bread of different compositions (whole grain, rye, barley and diet bread) at 24 hours intervals during three days after bread preparation were investigated by means of a MOM-color 100 tristimulus photo colorimeter, in CIE, CIELab, ANLAB and Hunter systems. The highest value of average reflectance y (%) was found for barley bread (immediately after preparation), so that can be said that this sample was “conditionally” the lightest. The lowest values of y (%) were found for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…The a* and b* values of control sample and bread containing 1% sesame oil showed decreases during storage, while those of breads with 2 or 3% added oil showed an increase. As it can be seen from Table 4, the rate of change of color parameters was lower in refrigerator than that in Popov-Raljić, Mastilović, Laličić-Petronijević, and Popov (2009) hypothesized the moisture loss as the cause of color change. They also concluded that the change in color is a direct consequence of staling.…”
Section: Bread Colormentioning
confidence: 68%
“…The a* and b* values of control sample and bread containing 1% sesame oil showed decreases during storage, while those of breads with 2 or 3% added oil showed an increase. As it can be seen from Table 4, the rate of change of color parameters was lower in refrigerator than that in Popov-Raljić, Mastilović, Laličić-Petronijević, and Popov (2009) hypothesized the moisture loss as the cause of color change. They also concluded that the change in color is a direct consequence of staling.…”
Section: Bread Colormentioning
confidence: 68%
“…As this project was shared back with the open-source scientific community the time for another group to build their own open-source COD instrument is estimated to be under 10 hours at a cost of approximately US$50.00. Similarly, the time for others to create an open-source colorimeter is also reduced for other applications [2232] such as: Measuring the concentration of some chemicals in a solution, quantifying observations of biological specimens, growth cultures, food science, quality control in manufacturing, diagnose some diseases, test the concentration of hemoglobin in blood, determining the efficacy of sun protection products, nephelometry for water quality, visibility, and global warming studies to measure global radiation balance, and many other applications. The open-source IORodeo colorimeter kit has already realized some of these applications for the educational environment [44], however, future work is necessary to design focused research tools for all of these applications.…”
Section: Resultsmentioning
confidence: 99%
“…The method requires a blank solution for calibration (zero) and reports results in absorbance units, transmittance or applies the Beer-Lambert law to report results as concentration [21]. Colorimetric methods are used widely in research and industry, including investigating food during storage such as bread [22], chocolate [23] and milk [24]. Colorimeters are used to monitor the levels of nitrates, phosphates, metals and other compounds present in effluent from the manufacture of paper and other commercial goods [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…These open-source tools can also be used as building blocks in tangential disciplines. So for example, the time for other research groups to create an open-source colorimeter following the details in Chapter 6 is also reduced for other applications beyond COD such as: measuring the concentration of some chemicals in a solution, quantifying observations of biological specimens, growth cultures, food science, quality control in manufacturing, diagnosis of diseases, testing the concentration of hemoglobin in blood, determining the efficacy of sun protection products, nephelometry for water quality, visibility, and global warming studies to measure global radiation balance, and many other applications [12][13][14][15][16][17][18][19][20][21][22]. The OpenSCAD code has been made available, making it easy to redesign the case to test, for example, alternative sizes or geometries of vials.…”
Section: Resultsmentioning
confidence: 99%